Jaringan Kerjasama Perpustakaan Perguruan Tinggi - Pranindita Dwi Fadhila; Mehlan Ainul Firdaus; Teguh Budimanta Tarigan; Yusniah Yusniah (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
Collaboration between libraries is carried out in order to build outstanding library services that focus on users. This library collaboration aims to increase activity across multiple resources, expand user and technical services, and enable wider access to the collection. Policy strategies, human resource development (HR), correlation, resource sharing, and information technology are some examples of cooperative development strategies. There are several variables that encourage and hinder the implementation of this collaboration. Increasing customer demand, technological advances, and continuous use are some of the elements that make this possible. Geographical distance from each other, lack of available corner space, and time are obstacles to cooperation. Keywords: Cooperation; Library; College